Spectrophotometric Determination of Vancomycin Hydrochloride (Batch and Flow-Injection) Using O-Nitroaniline as diazotized Chromogenic Reagent - Subhi Abed, Sadeem; T. Hussein , Omar (Iraqi Journal of Science, 2023)
New, simple and sensitive batch and nFIA spectrophotometric methods for the determination of Vancomycin Hydrochloride in pure form and in pharmaceutical preparations were proposed, These method's were based on diazotization and coupling reaction between Vancomycin Hydrochloride and diazotized O-nitroaniline in alkaline medium to form Orange water-soluble dye that is stable and has a maximum absorbance at 465nm. Acalibration graph shows that aBeer's law is obeyed over the concentration range of 0.8-60 and 5-400 μg.mL-1 of Vancomycin Hydrochloride with detection limit's of 0.16 and 1.666 μg.mL-1 of Vancomycin Hydrochloride for batch and nFIA methods, respectively. The FIA procedure sample throughput was 80 h-1. All different chemicals and physical experimental parameters affecting on the development and stability of the colored product were carefully studied, and the proposed methods were successfully applied for the determination of Vancomycin Hydrochloride in pharmaceutical preparations.